Seroprevalence of Antibodies against Human Herpesvirus 6 in the Quebec City Area - Louise Deschênes; Jean R Joly; Michel Couillard; Gilles Richer (Canadian Journal of Infectious Diseases)
Seroprevalence of antibodies against human herpesvirus 6 was determined in a sample of 303 randomly selected individuals from the Quebec City area. The influence of different variables on antibody litres was also evaluated. Human herpesvirus 6 was grown in the HSB-2 cell line, and antibody litres were measured by indirect immunofluorescence. Serum samples were collected from 177 females and 126 males ranging in age from two months to 88 years. Ninety-nine per cent (300 of 303) of this population had an antibody titre of at least 1:10, whereas 75% had a titre of at least 1:80. Women had a higher geometric mean litre than men (P=0.06). This difference between sexes varied according to age and became statistically significant in subjects older than 20 years of age (P=0.04). It was found that this difference was attributable to higher antibody litres in women in the 15 to 40 year age group who had previously had children.